Pelaksanaan Kegiatan Pengabdian Masyarakat Seminar Pemasaran Melalui Sosial Media bagi Ibu-Ibu Desa Pajangan Lamongan - Indriartiningtias, Retno (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2023)
This seminar is part of the thematic KKN activities carried out by the Trunojoyo University, Madura in Lamongan City, especially in Pajangan Village. Pajangan Village is one of the villages located in the city of Lamongan, East Java where the main livelihood of its citizens, especially the villagers' mothers, make songkok and make processed fruit. With the one-day seminar related to online marketing, especially through social media, it is hoped that it can become an alternative marketing method that has been using the getuk tular system (word of mouth), so that in the future it can contribute to increasing family income.